TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANTENATAL CARE: TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANTENATAL CARE - Munasifah, Munasifah; Windayanti, Hapsari (STIKES Telogorejo Semarang, 2023)
Background: The problem that occurs at the Banyubiru Health Center, Semarang Regency is that there are still pregnant women who do not fully know about Antenatal care, which affects the ANC coverage that has not been achieved at the Banyubiru Health Center, namely in July and August 2021 as many as 632 pregnant women target with an achievement target in July K1 58, 3%, K4 58.3% and K6 58.3%. In July there were 335 targets for pregnant women with achievements in K1 53%, K4 50.6% and K6 42.1%, and in August there were 388 targets for pregnant women with K1 66.6, K4 66.6%, and K6 66.6%. In August, the performance in K1 was 61.4%, K4 58.4% and K6 22.3%. The impact of not doing antenatal care checks will increase pregnant women with high risk due to lack of initial screening for screening pregnancy risks Research Objectives: To describe the level of knowledge of pregnant women about the meaning, purpose, benefits, service standards, and schedule of antenatal care visits. Methods: This study uses a quantitative descriptive research design, the number of samples is 35 respondents using a sampling technique using Simple Random Sampling with Stratified Random Sampling. The research instrument uses a questionnaire. Results: The results showed that the knowledge of pregnant women about antenatal care at the Banyubiru Health Center, Semarang Regency, was included in the sufficient category of 48.6%, with good knowledge of 25.7% and 25.7% with less knowledge. Conclusion: Based on the results of the study, it can be concluded that the knowledge of pregnant women about the definition of antenatal care is good as much as 77.1%. The majority of pregnant women's knowledge about the purpose of antenatal care is 51.4%. The majority of pregnant women's knowledge about the benefits of antenatal care is 57.1%. The majority of pregnant women's knowledge about antenatal care service standards is 42.9%. The majority of pregnant women's knowledge about antenatal care visits is 80% less.